2015
DOI: 10.3390/catal5010077
|View full text |Cite
|
Sign up to set email alerts
|

Supported Photocatalyst for Removal of Emerging Contaminants from Wastewater in a Continuous Packed-Bed Photoreactor Configuration

Abstract: Water pollution from emerging contaminants (ECs) or emerging pollutants is an important environmental problem. Heterogeneous photocatalytic treatment, as advanced oxidation treatment of wastewater effluents, has been proposed to solve this problem. In this paper, a heterogeneous photocatalytic process was studied for emergent contaminants removal using paracetamol as a model contaminant molecule. TiO2 photocatalytic activity was evaluated using two photocatalytic reactor configurations: Photocatalyst solid sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…The catalyst loads were 0.3 and 0.6 g L −1 , which are within the range reported in the literature [45,46]. In the first stage of the experimental runs, the samples from the reactor were taken at the beginning of the process and after the amount of UV energy reached 19.14 and 38.28 W h m −2 .…”
Section: Methodssupporting
confidence: 71%
“…The catalyst loads were 0.3 and 0.6 g L −1 , which are within the range reported in the literature [45,46]. In the first stage of the experimental runs, the samples from the reactor were taken at the beginning of the process and after the amount of UV energy reached 19.14 and 38.28 W h m −2 .…”
Section: Methodssupporting
confidence: 71%
“…The authors concluded that TiO2 resulted in photocatalytic activity for removing the compound from waste water. Forty two per cent of the EC was removed after 8 hours of exposure (Borges et al, 2015) Ultrasonic Irradiation:-Another advanced oxidation process being exploited and studied for increase efficiency and economical large scale application for removing emerging contaminants from wastewater streams is Ultrasonic Irradiation. The fascination with the catalytic effect of high energy frequencies (15 There have been a number of work which attempted to use the oxidative process in removing emerging contaminants, such as pharmaceuticals from solution.…”
Section: The Effects Of Emerging Pollutants:-mentioning
confidence: 99%
“…The photocatalytically active material, TiO 2 (Degussa P25, Evonik Industries), was examined by X-ray diffraction (XRD) in order to obtain the percentage of anatase and rutile phase. Nitrogen adsorptiondesorption porosimetry and mercury porosimetry techniques were used to study its specific surface area and textural properties [20]. TiO 2 (Degussa P25) was mainly composed by the photocatalytically active anatase phase, 81% (wt).…”
Section: Methodsmentioning
confidence: 99%